The burden of preserved ejection fraction heart failure in a real-world Swedish patient population. (January 2014) - Stålhammar, Jan; Stern, Lee; Linder, Ragnar; Sherman, Steve; Parikh, Rohan; Ariely, Rinat; Deschaseaux, Celine; Wikström, Gerhard
Abstract Objectives: To evaluate resource use and associated costs in patients with a diagnosis of heart failure with preserved ejection fraction (HF-PEF) in Sweden. Methods: This retrospective study identified real-world patients with an ICD-10 diagnosis code for heart failure (I50) for the period between July 1, 2005 and December 31, 2006 from electronic medical records of primary care centers in Uppsala County Council, and in the Swedish patient registry data. Patients were categorized as having HF-PEF (left ventricle ejection fraction [LVEF] > 50%) during the index period. The study assessed medication utilization, outpatient visits, hospitalizations, and associated healthcare costs, as well as the incidence rates and time to all-cause and heart failure mortality following the index period. Results: The study included 137 HF-PEF patients with a mean age of 77.1 (SD = 9.1) years. Over 50% of HF-PEF patients were female and hypertensive. Nearly all patients received ≥1 medication post-index. Patients had an average of 1.5 heart failure related hospitalizations per follow-up year. The average annual per patient cost for the management of a HF-PEF patient was found in Sweden to be Swedish Krona (SEK) 108, 246 (EURO [EUR] 11, 344). Hospitalizations contributed to more than 80% of the total cost. All-cause mortality over the 18-month study period was 25.5%, and more than 50% of these deaths occurred within 1 year of index. Limitations: Due to the limitations of registry data, it is not possible to confirm the HF diagnosis, and therefore the accuracy of registry records must be assumed. Other factors such as short follow-up time, the study-mandated LVEF assessment, and a lack of drug duration data may also have an impact on the study results. Conclusions: All-cause mortality was high in the HF-PEF population, with more than half of patients dying within 1 year of study follow-up. Study results also indicate that 60% of HF-PEF patients have ≥1 hospitalization during follow-up. Hospitalizations, especially heart failure related admissions, represent a substantial proportion of the total healthcare burden of patients with HF-PEF in Sweden.